New Recorded of Saltwater Crocodile Crocodylus porosus Schneider, 1801 from East Coast Mangrove Ecosystem in Surabaya, East Jawa, Indonesia - Sapto Andriyono; Agustin Sukistyanawati (Airlangga University, 2021)
A single specimen of saltwater crocodile Crocodylus porosus Schneider, 1801 (1.50 cm in length) was captured and photographed by a local fisherman by gill net at fishpond around mangrove ecosystem of east coast Surabaya on December 2020. The location where the estuarine crocodile caught is an important wetland area in Surabaya with an excellent mangrove cover. Wonorejo mangrove location is about 10 km from the centre of Surabaya, the second-largest city in Indonesia. This finding is considered as a first reported of C. porosus in Surabaya, and at the same time is proof of the importance of the mangrove area on the east coast of Surabaya as a habitat for wildlife that must be conserved appropriately. Routine monitoring of mangrove areas, including their wildlife, is essential so that they are not displaced by the development of the city which changes the land function to become a residential area.